The evolution of the principle of equal rights of spouses in Europe – selected issues on the example of Poland and Spain - Kostrzewa, Kacper (Kortowski Przegląd Prawniczy, 2024)
Today, the principle of equality of rights and obligations of spouses is a fundamental element of the international standard of marriage. It has evolved over the years, even in the pre-state period. Until the last century, the feature of equality was not common and only appeared in global and European legislation. According to the Convention for the Protection of Human Rights and Fundamental Freedoms, drawn up in Rome in 1950, men and women of marriageable age have the right to marry and found a family according to national law. However, it was not until Protocol No. 7 of 1984 that the equality of spouses in marriage was guaranteed. The very evolution of the principle of equality is also evident in the case law of the European Court of Human Rights. The evolutionary interpretation of the Convention, which implies an injunction to interpret the law in the light of the „conditions of today”, is the result of changes introduced in the national legislation of the parties to the Convention. In Poland, the principle of equality was introduced into family law as a result of Soviet influence in the decrees of 1945 and 1946, and later in the Family Code of 1950. In Western Europe, on the other hand, the equalisation of the legal situation of spouses did not occur until the 1960s and 1970s through numerous amendments. Poland and Spain were among the first countries to introduce the principle of equality of spouses into national legislation.